Prospective evaluation of soluble CD14 as a biomarker following five aflibercept treatments in diabetic macular edema - Hyungwoo Lee; Minsub Lee; Najung Kim; Nahee Kim; Dayoung Moon; Chanok Son; Hyewon Chung (Scientific Reports)
Abstract Using spectral-domain optical coherence tomography (SD-OCT) in patients with diabetic macular edema (DME), we studied the relationships between consecutive aflibercept treatments, soluble CD14 (sCD14) in the aqueous humor (AH), and anatomical features, including hyper-reflective foci (HFs) and other morphologic characteristics. This prospective study included 23 eyes of 23 patients with DME treated with five consecutive monthly intravitreal aflibercept injections. At each visit, sCD14 and VEGF levels in the AH were measured using ELISA. The number of HFs, central macular thickness (CMT), and volume of intraretinal fluid (IRF) and subretinal fluid (SRF) were also assessed. One month after fifth injections, there were significant decreases in CMT, the number of HFs, and the volumes of IRF and SRF. The level of sCD14 also decreased. Although sCD14 levels showed a downward trend, the change was not statistically significant. The group with reduced sCD14 exhibited improvements in all the factors, including visual acuity. In contrast, the group with increased sCD14 only showed significant decreases in CMT. When the data were categorized into two groups based on the final visual outcome, patients with good final visual acuity had consistently lower levels of sCD14 at all visits. This study highlights sCD14 as a potential biomarker for assessing treatment response to aflibercept in DME.